2023
DOI: 10.1177/01979183231154559
|View full text |Cite
|
Sign up to set email alerts
|

Internal and International Migration and the Mental Health of “Left-Behind” Older Parents

Abstract: Despite evidence of the impact of adult children's migration on left-behind older parents, the comparison of left-behind older parents’ mental health and psychological well-being between internal and international migration is limited. This article examines how the relationship between adult children's migration and parent's mental health differs according to the migrant's destination — only internal migration, only international migration, or hybrid migration (at least one child who migrated internally and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…The empirical evidence on the relationship between the migration of a family member and the mental health of the remaining members suggests mixed results that vary depending on the characteristics of migrants, their family and their context. Among elderly parents, the impact varies depending on, among other things, the frequency of contact with the migrant child, interactions with other adult children, and availability of a local support network (Kumar, 2021;Thapa et al, 2023). In a review of mostly crosssectional correlational studies, Thapa et al (2018) concluded that left-behind older parents had higher levels of mental health problems than did elderly parents with migrant children.…”
Section: Emigration Of a Family Membermentioning
confidence: 99%
“…The empirical evidence on the relationship between the migration of a family member and the mental health of the remaining members suggests mixed results that vary depending on the characteristics of migrants, their family and their context. Among elderly parents, the impact varies depending on, among other things, the frequency of contact with the migrant child, interactions with other adult children, and availability of a local support network (Kumar, 2021;Thapa et al, 2023). In a review of mostly crosssectional correlational studies, Thapa et al (2018) concluded that left-behind older parents had higher levels of mental health problems than did elderly parents with migrant children.…”
Section: Emigration Of a Family Membermentioning
confidence: 99%